Amniotic fluid clusterin in pregnancies complicated by the preterm prelabor rupture of membranes. (2nd November 2017) - Musilova, Ivana; Andrys, Ctirad; Drahosova, Marcela; Soucek, Ondrej; Pliskova, Lenka; Stepan, Martin; Bestvina, Tomas; Maly, Jan; Jacobsson, Bo; Kacerovsky, Marian
Abstract: Objective : The aim of this study was to evaluate clusterin concentrations in amniotic fluid in pregnancies complicated by preterm prelabor rupture of membranes (PPROM) with respect to the presence of the microbial invasion of the amniotic cavity (MIAC), intra-amniotic inflammation (IAI) and microbial-associated IAI. Methods : One hundred thirty-six women with singleton pregnancies complicated by PPROM were included in this study. Amniotic fluid samples were obtained by transabdominal amniocentesis. Amniotic fluid clusterin concentrations were assessed by enzyme-linked immunosorbent assay. MIAC was determined by a non-cultivation approach. IAI was defined as an amniotic fluid bedside interleukin-6 concentration ≥745 pg/mL. Microbial-associated IAI was characterized as the presence of both MIAC and IAI. Result : Women with MIAC, IAI and microbial-associated IAI had lower amniotic fluid clusterin concentrations than women without these complications (with MIAC: median 1314 ng/mL versus without MIAC: median 1633 ng/mL, p = 0.003; with IAI: median 1281 ng/mL versus without IAI: median 1575 ng/mL, p = 0.04; with microbial associated-IAI: median 1220 ng/mL versus without microbial-associated IAI: median 1575 pg/mL; p = 0.008). A week negative correlation between amniotic fluid clusterin concentrations and gestational age at sampling was revealed (rho= −0.30; p = 0.0005). Conclusions : The presence of MIAC, IAI and microbial-associated IAI was characterized by lower amniotic fluid clusterin concentrations in pregnancies complicated by PPROM.